A STUDY ON IDIOMATIC EXPRESSIONS CONTAINING THE WORD “WATER” IN ENGLISH AND “NƯỚC” IN VIETNAMESE - Nguyễn Văn Khiếu (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis attempts to study syntactic and semantic features of English idiomatic expressions containing the word “Water” in English (EIW) and “nước” in Vietnamese (VIN). Both qualitative and quantitative analysis is made use of through 200 idioms in English and Vietnamese together with numerous numbers of examples from various linguistic books, short stories, and other sources on the internet. The findings show that idiomatic expressions containing the word “Water” in English and “nước” in Vietnamese have remarkable syntactic and semantic features. The study also points out some similarities and differences between EIW and VIN in some features. Simultaneously, the study also deals with the implications for teaching and learning of idioms as well as for further studies.